(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present studies focus on identification of bioactive compounds from methanolic extraction of Smilax perfoliata and Breynia retusa by GC–MS analysis and also evaluated the phytochemical constituents present in S. perfoliata and B. retusa methanolic extraction. In-vitro antioxidant activity (hydroxyl radaical scavenging activity, determination of reducing power, metal chelating activity, carbon tetrachloride (CCl4) induced lipid peroxidation, inhibitory test on protein oxidative modification, lipid peroxidation assay, catalase assay and reduced glutathione assay) was evaluated by adopting different methods. Phytochemical screening of the methanolic extraction of S. perfoliata and B. retusa revealed the presence of flavonoids, phenolic compounds, triterpenoids, tannins, saponins, amino acids, proteins, steroids and carbohydrates gas chromatography-mass spectrometry (GC-MS) analysis of the methanol extract of S. perfoliata has shown the presence of different bio active compounds. A total of 24 compounds were identified in methanolic extract composition S. perfoliata showed bio active compounds like propanimidamide, N-(1-chloro-1-propenyl)-, monohydrochloride, 5-bromo-8-(5-nitrosalicylideneamino) quinoline hydrochloride, nitrogen fluoride (N2F2), (Z)-20 1.426, 2,4,6-cycloheptatrien-1-one, hexahydro-isobenzofuran-1-one, ethene, 1-(2-methoxy-,3,5-dibromophenyl)-2-nitro- was found. And B. retusa showed bio active compounds like acetyl bromide, N, N’-ethylenebis (N-nitroacetamide), 2-propanone, 1,1-dichloro-, N,N’-ethylenebis(N-nitroacetamide), 2-propanone, 1,1-dichloro-methane, chlorotrinitro- was found. These compounds are responsible for the different therapeutic and pharmacological properties. Methanolic extraction of S. perfoliata and B. retusa possesses antioxidant activity.